2014
DOI: 10.1016/j.trsl.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 expression is associated with tumor aggressiveness and outcomes in patients with bladder cancer: a correlation with smoking intensity

Abstract: Heme oxygenase (HO)-1 is upregulated in malignancies and, in turn, regulates other cancer-related factors. Although HO-1 expression has been associated with cigarette smoking under various pathologic conditions, little is known about their association in patients with bladder cancer. HO-1 expression was assessed in 215 formalin-fixed bladder cancer specimens by immunohistochemistry. Microvessel density, lymph vessel density (LVD), proliferation index (PI), and expression of the vascular endothelial growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 44 publications
2
41
1
Order By: Relevance
“…However, HO-1 expression was not observed to be associated with VEGF expression, as determined by univariate analysis. This result conflicts with the results of previous studies (17,35), which reported that VEGF, particularly VEGF-C and -D, were demonstrated to induce lymphangiogenesis. Therefore, HO-1 may stimulate lymphangiogenesis through mechanisms independent of VEGF signaling.…”
Section: Metastasiscontrasting
confidence: 99%
See 3 more Smart Citations
“…However, HO-1 expression was not observed to be associated with VEGF expression, as determined by univariate analysis. This result conflicts with the results of previous studies (17,35), which reported that VEGF, particularly VEGF-C and -D, were demonstrated to induce lymphangiogenesis. Therefore, HO-1 may stimulate lymphangiogenesis through mechanisms independent of VEGF signaling.…”
Section: Metastasiscontrasting
confidence: 99%
“…Concordant with previous reports (17,34), HO-1 expression is significantly and independently associated with COX-2 expression, which was determined using a multivariate model that included various other pathological features. However, HO-1 expression was not observed to be associated with VEGF expression, as determined by univariate analysis.…”
Section: Metastasismentioning
confidence: 52%
See 2 more Smart Citations
“…Previous studies have demonstrated that heme oxygenase-1 (HO-1) is up-regulated in malignancies and subsequently regulates tumor aggressiveness and various cancer-related factors [12,13]. Inducible HO-1 belongs to a member of the heat shock protein family, which catalyzes the rate-limiting step of heme degradation into bilirubin, carbon monoxide (CO) and ferrous iron.…”
Section: Introductionmentioning
confidence: 99%